Ethics, data governance, knowledge production and public engagement in population data science field from the perspective of a brazilian experience - Almeida, Bethânia de Araújo (2024)
Fundação Oswaldo Cruz. Instituto Gonçalo Moniz. Centro de Integração de Dados e Conhecimento para a Saúde. Salvador, BA, Brasil.